2012
DOI: 10.1007/s10384-012-0214-8
|View full text |Cite
|
Sign up to set email alerts
|

Quadrantal macular retinal thickness changes in strabismus subjects with abnormal binocular vision development

Abstract: Dominant eyes of the strabismus group with abnormal binocular vision development exhibited thinner superior temporal GCC thicknesses in the 3-mm region. Retinal ganglion cells in this region might be affected by efferent neural degeneration that originates in the visual pathway responsible for adaptations to the visual experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Unlike other studies, Oka et al. [10] reported that the dominant eyes of patients with strabismus who had developed abnormal binocular vision had thinner superior temporal quadrantal macular thickness values.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Unlike other studies, Oka et al. [10] reported that the dominant eyes of patients with strabismus who had developed abnormal binocular vision had thinner superior temporal quadrantal macular thickness values.…”
Section: Discussionmentioning
confidence: 84%
“…This study was motivated by recent reports revealing interocular quadrant macular thickness, refractive error, and axial length differences in sighting ocular dominance [10,11]. Because the macula is the retinal area concerned with central vision and is the primary determinant of visual output to the visual cortex, we hypothesized that it might complement the brain's primary role in the mechanism of ocular dominance.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon can cause suppression or potentially abnormal retinal correspondence [ 7 11 ]. In reports of strabismic patients with abnormal binocular vision development, OCT exhibited changes in macular retinal thickness [ 1 ]. Retinal thickness was correlated with retinal perfusion for both healthy subjects and amblyopia [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, concomitant strabismic patients with normal visual acuity were generally considered to have normal macular structure. However, recent studies have revealed morphological changes in the macular of strabismic patients, including thickened outer retinal layers in XT patients according to optical coherence tomography (OCT) [ 1 , 2 ]. Furthermore, known relationships exist between retinal thickness and retinal perfusion in healthy subjects [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…(10)(11)(12)(13) Several studies have demonstrated that inconsistent macular structure changes in the deviated eye in strabismus, which includes increased central macular thickness postoperatively and decreased total macular thickness of the dominant eye, although these pathoanatomical ndings have not been con rmed. (14,15) However, macular OCTA ndings in large angle exotropia with abnormal binocular vision have not been reported. The study aimed to use OCTA to assess macular microvasculature and the foveal avascular zone (FAZ) in large exodeviation patients with abnormal binocular vision.…”
mentioning
confidence: 99%